UJI STABILITAS FISIK SECARA ORGANOLEPTIS PEMBUATAN SEDIAAN MINYAK GOSOK DARI BAHAN KELAPA (Cocos nucifera L.), SERAI (Cymbopogon citratus DC.) DAN DAUN JERUK NIPIS (Citrus aurantifolia) - Andriani, Susi; Sulisiyanti, Ebih (Journal of Holistic and Health Sciences (Jurnal Ilmu Holistik dan Kesehatan), 2017)
Background: Virgin Coconut Oil (VCO) from pure coconut oil is now widely used by the community as a liniment, mixing VCO as an abrasive oil with the addition of lemongrass and lime leaves can add to its usefulness and usefulness. Objective: This study aims to see the stability of scrub oil after 4, 6 and 8 weeks in sealed containers as well as to provide practical preparations of natural materials that can be used by people with easy, cheap and practical manufacturing techniques. Methods: This is a descriptive study that has been used for generations. The preparation is carried out through a four-day deposition process using a water solvent. Rubbing oil is made with one kilogram of coconut which is shredded and added one liter of water for two squids, the coconut milk is obtained 1000ml and the filter is filtered, the filter for three days produces 400ml of pure coconut oil, after the pure coconut oil (VCO) added lemongrass (Cymbopogon citratus DC.) as much as 25gram and lime leaves (Citrus aurantifolia.) 25grams that have been cut into pieces for one day then filtered and yielded a rubbing oil made 3 bottles with each weight 100ml. Result: The organoleptic test of the preparation was carried out for 4, 6 and 8 weeks with the result showing that there was no fungal growth and physical changes that occurred physically from the color, flavor, and consistency shape, while for the odor of the rubbing oil had decreased the smell of lemongrass and orange nipis. It can be said that within 8 weeks the rubbing oil can be used safely. Conclusion: The preparation of abrasive oil as a treatment of skin health by organoleptic testing for 8 weeks can be used safely.